Articulating Problems and Markets: A Translation Analysis of Entrepreneurs' Emergent Value Propositions. (October 2018) - Spinuzzi, Clay; Altounian, David; Pogue, Gregory; Cochran, Robert; Zhu, Lily
In this qualitative study, the authors apply Callon's sociology of translation to examine how new technology entrepreneurs enact material arguments that involve the first two moments of translation—problematization (defining a market problem) and interessement (defining a market and the firm's relationship to it)—which in turn are represented in a claim, the value proposition. That emergent claim can then be represented and further changed during pitches. If accepted, it can then lead to the second two moments of translation: enrollment and mobilization. Drawing on written materials, observations, and interviews, we trace how these value propositions were iterated along three paths to better problematize and interesse, articulating a problem and market on which a business could plausibly be built. We conclude by discussing implications for understanding value propositions in entrepreneurship and, more broadly, using the sociology of translation to analyze emergent, material, consequential arguments.